THE CONCEPT OF BUSINESS ETIQUETTE AND BUSINESS COMMUNICATION (American Journal of Business Management, Economics and Banking, 2023)
This article provides information on the topic "Business etiquette: personal and written communication". The types and principles of business communication are given.